2004
DOI: 10.1111/j.1464-5491.2004.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of diabetic ketoacidosis in Pakistani adults with Type 2 diabetes mellitus

Abstract: This report highlights the need for the growing recognition of DKA occurring in adults with Type 2 DM in the South Asian population. Mortality rates are unacceptably high but the majority of survivors remain insulin independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 16 publications
5
42
3
Order By: Relevance
“…Similar results were found in a study in Pakistan. 12 In this study three patients had severe hyponatraemia, 4 patients had severe hypokalaemia and 5 patients had severe acidosis. But, after treatment initiation, many patients developed hypokalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a study in Pakistan. 12 In this study three patients had severe hyponatraemia, 4 patients had severe hypokalaemia and 5 patients had severe acidosis. But, after treatment initiation, many patients developed hypokalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Almost similar picture was seen in different studies throughout the world. 13-18 Jabbar A et al 19 found that in twothird of type 2 diabetic patients, DKA was precipitated by infection and after recovery from DKA; many of them were on OADs without recurrence of DKA. This observation explains that infection can unmask previously undiagnosed type 2 diabetic patients, as reported by Pinto ME et al 17 In different studies it was found that, in up to 25% of patients with DKA precipitating cause could not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…12 SAMJ Diabetic hyperglycaemic crisis is a major reason for high-care unit admissions, 1 with mortality rates of up to 30%. [2][3][4][5][6][7][8][9] It is characteristically classified as ketoacidotic or hyperosmolar. 10 Presentations with the combination of ketoacidosis and hyperosmolality are recognised, 6,7,[11][12][13][14][15][16] and have variably been described as ketoacidosis with hyperosmolality or hyperosmolar state with ketoacidosis, depending on whether ketoacidosis or hyperosmolality was considered dominant.…”
mentioning
confidence: 99%